Hand-held dynamometry: tester strength is paramount, even in frail populations. - KENNY, ROSE ANNE (My University, 2011)
To determine test-retest and inter-rater reliability of hand-held dynamometry when used to measure knee--extensor strength in patients with advanced cancer. SUBJECTS: Adults with metastatic or locally advanced cancer recruited from palliative care services to a study of the risk factors for falls. METHODS: Consecutive recruits (n?=?30) underwent repeat testing after an interval of 1 h, by the same researcher, to assess test-retest reliability. The subsequent 15 patients underwent retesting by a second researcher. The intra-class correlation coefficient and limits of agreement were calculated. RESULTS: The test-retest reliability difference between measurements increased with the magnitude of measurement, mean leg strength?=?113 N (standard deviation 43.1), 95% ratio limits of agreement 0.81-1.5, intra-class correlation coefficient?=?0.9. The inter-rater testing mean leg strength?=?128.5 N (standard deviation 35.1), 95% limits of agreement?=?-57.24 to 36.06 N. Intra-class correlation coefficient?=?0.83. CONCLUSION: Test-retesting and inter-rater testing yielded high intra-class correlation coefficients, but the limits of agreement were wide. In test-retesting, the difference between tests increased as the magnitude of measurement increased. It has been widely reported that hand-held dynamometry is reliable when used to measure knee-extensor strength in frail or elderly persons. However, our results show that, even in these populations, reliability may be compromised by inadequate tester strength.
PUBLISHED
Keywords: Gerontology; hand-held dynamometry